Effects of Storage Period of Waste Frying Oil to Biodiesel Conversion - Luchis Rubianto; Sudarminto Setyo Yuwono; Atikah Atikah; Soemarno Soemarno (Program Pascasarjana Universitas Brawijaya, 2015)
Waste frying oil is a material that potentially harmful to environment. It is also harmful to human health as suspected being a carcinogenic material. Alternatively, the oil can be used as raw material to produce renewable fuel. Storing the oil in an open container increases free fatty acids due to oxidation. Higher acids content makes more complicated in transesterification process and decreases conversion percentage. Objective of this experiment was to determine effects of storage period of waste frying oil to biodiesel conversion. The waste frying oil was originally from palm oil. In this experiment, the oil was used by two different home industries producing cassava crisps and fried bread. Each type of oil was stored in open space with period from 0 day to 90 days. The oil was converted to fatty acid methyl ester or biodiesel, a renewable fuel to replace petroleum diesel fuel, by means of alkaline process using potassium hydroxide as catalyst. Gas chromatography was used to analyze percentage of the biodiesel produced. By storing the waste frying oil to 90 days, conversion percentage decrease from 95 to 79% for waste frying oil from cassava crisps industry. Meanwhile, for the oil from fried bread industry, the figure decrease from 92 to 71%. It was found that the longer storage period the lower was the biodiesel conversion . Keywords: Free Fatty Acid, Storage Period, Transestrification, Waste Frying Oil